The Effect of Scientific Approach Combined with P.L.A.N Technique Viewed from Text Genre on The Tenth Grade Students’ Reading Competency at SMA Negeri 1 Penebel - ., NI PUTU DIAN INDRA PRATIWI; ., PROF. DR. DEWA KOMANG TANTRA, M.Sc.; ., DR. NI MADE RATMININGSIH, M.A. (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2016)
The aims of the research were to investigate: 1) the effect of Scientific Approach combined with P.L.A.N technique on the tenth grade students? reading competency, and 2) the difference of the effect of Scientific Approach combined with P.L.A.N technique viewed from text genre on the tenth grade students? reading competency. This research was an experimental research with Post-Test Only Control-Group Design. The population of the study was 6 classes (198 students) of the tenth grade students of SMA Negeri 1 Penebel in academic year 2015/2016, in which two classes were the samples of this research which was assigned into two groups, one class with 34 students as the control group (Scientific Approach without P.L.A.N) and one class with 34 students as experimental group (Scientific Approach combined with P.L.A.N technique). The two groups were determined by using Cluster Random Sampling technique. The data were collected through reading competency test, and were analyzed by applying One-Way ANOVA. In line with the research questions, the results shows that there is statistically significant effect of Scientific Approach combined with P.L.A.N technique on the tenth grade students? reading competency. Besides, there is no significant difference of the effect of Scientific Approach combined with P.L.A.N technique viewed from text genre (i.e. descriptive, narrative, recount) on the tenth grade students? reading competency. These results provide empirical evidence of the importance of implementing the specific teaching strategies of Scientific Approach combined with P.L.A.N technique in improving students? reading competency.Kata Kunci : Scientific Approach, P.L.A.N (Predict, Locate, Add, Note) technique, text genre, reading competency. Fokus penelitian ini adalah untuk mengetahui; 1) pengaruh pendekatan ilmiah yang dikombinasikan dengan teknik P.L.A.N terhadap kompetensi membaca siswa kelas X di SMA Negeri 1 Penebel, dan 2) perbedaan pengaruh pendekatan ilmiah yang dikombinasikan dengan teknik P.L.A.N ditinjau dari jenis teks terhadap kompetensi membaca siswa kelas X di SMA Negeri 1 Penebel. Penelitian ini adalah penelitian eksperimen dengan bentuk rancangan Post-Test Only Control-Group Design. Populasi penelitian ini adalah 6 kelas dari kelas X SMA Negeri 1 Penebel tahun ajaran 2015/2016 yang terdiri dari 198 siswa, dimana dua kelas merupakan sampel dari penelitian ini yang menjadi dua kelompok, satu kelas yang terdiri 34 orang siswa sebagai kelompok control (Pendekatan Ilmiah tanpa menggunakan teknik P.L.A.N), dan satu kelas yang terdiri dari 34 siswa sebagai kelompok eksperimen (Pendekatan Ilmiah dengan teknik P.L.A.N). Penentuan sampel ditentukan dengan menggunakan teknik Cluster Random Sampling. Data dalam penelitian ini dikumpulkan melalui tes kompetensi membaca, dan kemudian dianalisa dengan One-Way ANOVA. Hasil penelitian menunjukkan bahwa secara statistik terdapat pengaruh yang signifikan dari strategi pendekatan ilmiah dengan teknik P.L.A.N terhadap kemampuan membaca siswa kelas X SMA Negeri 1 Penebel, dan tidak terdapat perbedaan yang signifikan dari pengaruh strategi pendekatan ilmiah dengan teknik P.L.A.N ditinjau dari jenis teks terhadap kemampuan membaca siswa kelas X SMA Negeri 1 Penebel ditinjau. Hasil penelitian ini dapat dijadikan bukti empiris tentang pentingnya penerapan strategi pendekatan ilmiah yang dikombinasikan dengan teknik P.L.A.N dalam upaya meningkatkan kompetensi membaca siswa.keyword : Pendekatan Ilmiah, teknik P.L.A.N (Predict, Locate, Add, Note), teks, kompetensi membaca.